Zen und die Kunst des Schwimmen – Ästhetische Erfahrung als neue Perspektive für das Techniktraining - Dahl, Dagmar Gerda Martha (Revija za elementarno izobraževanje, 2016)
Zen and the Art of Swimming – Aesthetical Experience as a New Perspective for Training Technique. The interest in alternative movement concepts has been on the increase in recent years. Mindfulness is well known in sports psychology, and many sports have been promoted as ‘Zen sports’. The use of the phrase ‘Zen and the Art of ...’ has also become commonplace. People learning and teaching swimming techniques face unique challenges due to the special conditions that water provides. The approach based on looking at swimming as a Zen sport, or as an art in the sense of being a sensual aesthetic experience, and an aesthetic learning process, can provide new teaching and learning opportunities. Gadamer’s, Dewey’s, and Johnson’s philosophical concepts combined with approaches of embodiment theories and theories of aesthetic learning processes (Storch, Stelter, Gallagher) have been brought together with the basic elements from Zen and supplemented and exemplified with practical examples.
Keywords: Zen; art; swimming; aesthetical experience; learning